Critical role of the HDAC6–cortactin axis in human megakaryocyte maturation leading to a proplatelet-formation defect. Issue 1 (December 2017) - Messaoudi, Kahia; Ali, Ashfaq; Ishaq, Rameez; Palazzo, Alberta; Sliwa, Dominika; Bluteau, Olivier; Souquère, Sylvie; Muller, Delphine; Diop, Khadija; Rameau, Philippe; Lapierre, Valérie; Marolleau, Jean-Pierre; et al.
Abstract Thrombocytopenia is a major side effect of a new class of anticancer agents that target histone deacetylase (HDAC). Their mechanism is poorly understood. Here, we show that HDAC6 inhibition and genetic knockdown lead to a strong decrease in human proplatelet formation (PPF). Unexpectedly, HDAC6 inhibition-induced tubulin hyperacetylation has no effect on PPF. The PPF decrease induced by HDAC6 inhibition is related to cortactin (CTTN) hyperacetylation associated with actin disorganization inducing important changes in the distribution of megakaryocyte (MK) organelles. CTTN silencing in human MKs phenocopies HDAC6 inactivation and knockdown leads to a strong PPF defect. This is rescued by forced expression of a deacetylated CTTN mimetic. Unexpectedly, unlike human-derived MKs, HDAC6 and CTTN are shown to be dispensable for mouse PPF in vitro and platelet production in vivo. Our results highlight an unexpected function of HDAC6–CTTN axis as a positive regulator of human but not mouse MK maturation. Histone deacetylase (HDAC) inhibitors, a class of cancer therapeutics, cause thrombocytopenia via an unknown mechanism. Here, the authors show that HDAC6 inhibition impairs proplatelet formation in human megakaryocytes, and show that this is linked to hyperacetylation of the actin-binding protein cortactin.